Strategi Terminasi Dalam Proses Bimbingan Konseling Kelompok Belajar: Strategi Terminasi Dalam Proses Bimbingan Konseling Kelompok Belajar - Azhari; Rusnawati (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Termination in counseling guidance comes from two initiatives. First, the lecturer's initiative and second, the student's initiative, either negative or positive. Termination occurs, including the realization of hopes in the counseling guidance process and the failure to realize hopes in the counseling guidance process. both lecturer's initiative and student or student-based e-counseling initiative. This study aims to determine the strategies of lecturers or lecturers in implementing termination of counseling guidance in the learning process. Counseling termination is the last step for lecturers so that students understand that the counseling and guidance session will end. In it, there are various messages and reinforcements for students which are part of the last strategy as a hope that the message or teaching material can be implemented in the future by students or students. The method in this study uses an interpretive method. The results of this discussion indicate that the termination strategy for counseling guidance is outlined in two termination directions including: first termination at the end of the counseling guidance session. second termination at the end of the counseling guidance session. termination at the end of the counseling guidance session contains the following points: (a) the lecturer opens effective communication as a signal that the session will end (b) the lecturer opens opportunities for mentoring for students and closes with words of thanks, appreciation and prayer. Furthermore, termination at the end of counseling in which the lecturer prepares: (a) languages that lead students to understand that counseling will end. (b) the lecturer provides opportunities for discussion in the form of notes and questions to conclude the results (c) formal termination which ends with prayer. From the results of this study, the termination strategy can also be implemented in various learning models, both self-directed learning, contextual, cooperative, collaborative and so on.